2022
DOI: 10.1111/acel.13745
|View full text |Cite
|
Sign up to set email alerts
|

N‐homocysteinylation of α‐synuclein promotes its aggregation and neurotoxicity

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Aging is the most important risk factor for PD. Interestingly, we found that the levels of both Hcy and HTL in the mouse brain increased in an age‐related manner (Zhou et al., 2022 ). Consistently, IHC and Western blot analyses revealed that the level of DJ‐1 K182Hcy increased during aging in the brains of TgA53T mice (Figure 3e–h ).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Aging is the most important risk factor for PD. Interestingly, we found that the levels of both Hcy and HTL in the mouse brain increased in an age‐related manner (Zhou et al., 2022 ). Consistently, IHC and Western blot analyses revealed that the level of DJ‐1 K182Hcy increased during aging in the brains of TgA53T mice (Figure 3e–h ).…”
Section: Resultsmentioning
confidence: 94%
“…Protein N‐hcy can be labeled with azide probes (Chen et al., 2019 ; Zhou et al., 2022 ). To investigate whether DJ‐1 undergoes N‐hcy, we transfected HEK293 cells with plasmids encoding hemagglutinin (HA)‐tagged DJ‐1, and then exposed the cells to 0.1 mM HTL for 24 h. The cell lysates were subjected to chemical reaction with a biotin‐azide probe.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accumulation of Hcy-thiolactone is harmful because of its ability to modify protein lysine residues (6), which generates structurally- and functionally-impaired N -homocysteinylated ( N -Hcy)-proteins with proinflammatory, prothrombotic, and pro-amyloidogenic properties (7). Hcy-thiolactone and N -Hcy-proteins accumulate in mentally retarded CBS- and MTHFR-deficient patients (7) and are mechanistically linked to neurological diseases such as Alzheimer’s disease (AD) (8, 9), stroke (10), cognitive impairment (11), Parkinson’s disease (12), and neural tube defects (13, 14), as well as cardiovascular disease (15), cancer (1618), and rheumatoid arthritis (19).…”
Section: Introductionmentioning
confidence: 99%